Takhrij Hadits: Pemahaman, Metode, dan Tujuan - Ismail, Nurjannah; Hidayat , Encang Sarip (El-Sunan: Journal of Hadith and Religious Studies, 2023)
Hadith, as one of the sources of Islamic law, plays a crucial role in guiding the Muslim community. However, the level of certainty regarding hadith varies; some are mutawatir with a authority comparable to the Quran, while others are ahad, requiring further research into the characteristics of their narrators. This study aims to comprehensively describe the intricacies of takhrij hadith and illustrate the significance of this research in maintaining the integrity of hadith as one of the primary sources of Islamic law. Through this study, it can be identified that a profound understanding of the characteristics of hadith, the status of narrators, and the authenticity of hadith is crucial. The process of takhrij provides rich information about the chain of transmission (sanad) and the content (matn) of hadith. Takhrij of hadith is not merely a method; it is also a holistic approach that opens a window to a profound understanding of the scholarly heritage of Islam. ABSTRAK Hadis sebagai salah satu sumber hukum Islam, memiliki peran penting dalam membimbing umat Muslim. Namun, tingkat kepastian hadis berbeda-beda; ada yang mutawatir dengan otoritas serupa Al-Quran, dan ada yang ahad, memerlukan penelitian lebih lanjut terkait sifat-sifat perawinya. Kajian ini bretujuan untuk mendeskripsikan tentang seluk-beluk takhrij hadis dan pentingnya penelitian ini dalam menjaga integritas hadis sebagai salah satu sumber utama hukum Islam. Dari kajian ini dapat diketahui bahwa pemahaman mendalam mengenai sifat-sifat hadis, status perawi, dan autentisitas hadis merupakan hal yang sangat penting. Proses takhrij memberikan informasi yang kaya tentang keadaan sanad dan matan hadis. takhrij hadist bukan hanya sekedar metode, tetapi juga suatu pendekatan holistik yang membuka jendela menuju pemahaman yang mendalam terhadap warisan keilmuan Islam.